Challenges on distance learning interaction among accounting students at state-run college in an island province in the Philippines / Rommel A. Avillanoza … [et al.] - Avilanoza, Rommel A.; Pandino, April Jane B.; Cruz, Chrystal M.; Cruz, Edmelyn B.; Topado, Jo-Ann S. (Research Management Institute (RMI), 2022)
Distance learning became more evident during the covid-19 pandemic. It became mandatory in different parts of the world just to continue the educational system despite the insufficiency of resources. This paper aimed to determine the challenges encountered by accounting students towards distance learning and their distance-learning interaction. The researchers used descriptive-correlational research. The data was gathered from 100 accounting students in a state-run college in an island province using a structured survey questionnaire and a simple random sampling technique. The study found that accounting students encountered a large extent of challenges in infrastructural limitations and state of mind while learner-learner interaction scored the highest among the types of distance learning interactions. The study also found that challenges encountered were in terms of disturbance in execution, the gap between people, and technological inhibitions having a significant and positive correlation with learner-content interaction. A negative correlation between challenges encountered in terms of the state of mind and learning-instructor interaction was also observed. The findings of the study can be used in enhancing the learning experience of the students and improvement of the learning management of the institution when implementing distance learning education.